Incubation time effect on releasing available phosphorus in saline sandy soil as a function of bone char application - Amin, Abu El-Eyuoon Abu Zied (Scientific reports, 2025)
To face the current crisis in global fertilizer prices, especially in developing countries where their food security has been greatly affected, alternative sources must be found for phosphate fertilizers, whose main source is phosphate rock, which is non-renewable and subject to depletion. Therefore, this study aims to evaluate the effect of the incubation period on the availability and fractionation of phosphorus in saline sandy soil under bone char addition. About 100 g of soil was placed in an airtight plastic jar and mixed thoroughly by adding 0.4 g of bone char. This experiment was incubated for 7, 16, 35, 65, and 84 days. The results obtained from this study revealed a significant increase ( p ≤ 0.01) in available phosphorus with applying bone char in saline soil after 7, 16, and 35 days of incubation compared to the initial soil (before the incubation and unamended). Relative to the initial soil, the concentration of available phosphorus increased by 33.7%, 19.5%, and 12.3% after 7, 16, and 35 days, respectively. The results showed that increasing the incubation time significantly decreased phosphorus availability in saline soil after bone char application. The NaHCO 3 -Pi, HCl-Pi, and Res-Pi fractions increased significantly with the addition of bone char to the soil under study at all incubation periods compared to the initial soil. Inorganic phosphorus fractions after bone char application to saline sandy soil followed the order of HCl-Pi > Res-P > NaHCO3-Pi > NaOH-Pi > NH 4 Cl-Pi. In this context, these findings concluded that bone char amendment could be a potential P-source for agriculture in saline sandy soils to confront the high prices of phosphate fertilizers.